2014
DOI: 10.2139/ssrn.2557362
|View full text |Cite
|
Sign up to set email alerts
|

Who Becomes a Tenured Professor, and Why? Panel Data Evidence from German Sociology, 1980-2013

Abstract: Prior studies that try to explain who gets tenure and why remain inconclusive, especially on whether non-meritocratic factors influence who becomes a professor. On the basis of career and publication data of virtually all sociologists working in German sociology departments, we test how meritocratic factors (academic productivity) as well as nonmeritocratic factors (ascription, symbolic, and social capital) influence the chances of getting a permanent professorship in sociology. Our findings show that getting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
(24 reference statements)
0
12
0
2
Order By: Relevance
“…To sum up, ours is the first study to use a virtually complete sample of all German academic political scientists to show that women tend to be favored over men in the hiring process for tenured professorships, before and after controlling for various factors, most importantly productivity (but see [ 65 , 66 ] for the discipline of sociology in Germany). This means that women get hired with fewer measurable publications than men do, indicating that there is no bias against women when judging their competency, different from what other studies found [ 20 : 342, 44 : 3].…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, ours is the first study to use a virtually complete sample of all German academic political scientists to show that women tend to be favored over men in the hiring process for tenured professorships, before and after controlling for various factors, most importantly productivity (but see [ 65 , 66 ] for the discipline of sociology in Germany). This means that women get hired with fewer measurable publications than men do, indicating that there is no bias against women when judging their competency, different from what other studies found [ 20 : 342, 44 : 3].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of archival promotion data found that women in IT were more likely to be promoted than men, contrary to the researchers’ predictions (Langer et al., 2020). Among German sociologists, women can get tenure with 23–44% fewer publications than men (Lutter & Schröder, 2016). …”
Section: Bias and Discrimination In The Workplacementioning
confidence: 99%
“…Hier zeigt sich, dass Berufungen beeinflusst werden von Forschungsleistungen (zugeschrieben durch Publikationen und Drittmitteleinwerbungen) und Lehrqualitäten (markiert durch Lehrevaluationen) (Kleimann et al 2015;Lutter und Schröder 2014;Plümper und Schimmelpfennig 2007). Hier zeigt sich, dass Berufungen beeinflusst werden von Forschungsleistungen (zugeschrieben durch Publikationen und Drittmitteleinwerbungen) und Lehrqualitäten (markiert durch Lehrevaluationen) (Kleimann et al 2015;Lutter und Schröder 2014;Plümper und Schimmelpfennig 2007).…”
unclassified
“…Die entscheidende Rolle des empirischen Zugriffs zeigt sich zum Beispiel beim Faktor Geschlecht: Während quantitative Längsschnittanalysen von Lebenslaufdaten weder für die Politikwissenschaft (Plümper und Schimmelpfennig 2007) noch für die Soziologie (Mau und Huska 2010;Lutter und Schröder 2014) eine systematische Benachteiligung von Frauen nachweisen (anders sieht das bei Müttern aus), können qualitative Studien, die auf teilnehmender Beobachtung und Experteninterviews beruhen, differenziertere Aussagen treffen. Die entscheidende Rolle des empirischen Zugriffs zeigt sich zum Beispiel beim Faktor Geschlecht: Während quantitative Längsschnittanalysen von Lebenslaufdaten weder für die Politikwissenschaft (Plümper und Schimmelpfennig 2007) noch für die Soziologie (Mau und Huska 2010;Lutter und Schröder 2014) eine systematische Benachteiligung von Frauen nachweisen (anders sieht das bei Müttern aus), können qualitative Studien, die auf teilnehmender Beobachtung und Experteninterviews beruhen, differenziertere Aussagen treffen.…”
unclassified